Socio-Ecologically Constituted Types of Sexual Assault. (March 2021) - Walsh, Kate; Sarvet, Aaron L.; Khan, Shamus; Choo, Tse-Hwei; Wall, Melanie; Santelli, John; Wilson, Patrick; Gilbert, Louisa; Reardon, Leigh; Hirsch, Jennifer S.; Mellins, Claude Ann
Despite the burden of sexual assault on college campuses, few effective prevention programs exist. Understanding the socio-ecological context in which sexual assaults occur may illuminate novel pathways to augment prevention. We examined data from 349 students at two inter-connected urban universities who completed a population-based survey ( N = 1, 671) and described at least one incident of sexual assault victimization. Using latent class analysis of 13 incident, relationship, and social context characteristics, we identified three types of sexual assaults: Incapacitation, Known Assailant, both Drinking; Verbal Coercion, Partner/Friend, Private; and Unwanted Touching, Stranger, Public. Incapacitation, Known Assailant, both Drinking incidents often involved survivor incapacitation with someone known to the victim following a party. Verbal Coercion, Partner/Friend, Private incidents often involved verbal coercion and intimate partners, with others rarely present prior to the assault. Unwanted Touching, Stranger, Public incidents often involved unwanted touching and strangers in a public place. Findings suggest three distinct sexual assault types, defined by different incident, relational, and socio-contextual factors, and reinforce the importance of disaggregating sexual assault to tailor prevention programs more effectively. Campus policy-makers and providers should be aware that each type of assault may require different prevention approaches. Online slides for instructors who want to use this article for teaching are available on PWQ's website athttp://journals.sagepub.com/doi/suppl/10.1177/0361684320964452